Developing effective teaching in Higher Education - Cristina Coggi; Paola Ricchiardi (Firenze University Press, 2018)
This contribution aims to develop a reflection on the complexity of the functions attributed to a university professor today. It will therefore focus on the analysis of didactic skills, emphasizing their social relevance and the need to form them adequately, at the beginning of academic careers, and to support them in the professional exercise. It will therefore be possible to identify, on the basis of international research results, the features that should have a course for the training of University teachers that can prove effective in promoting innovative didactic skills, with a view to increasing the quality of student learning. We propose an initial training model experimented with positive results at the University of Turin. Sviluppare un insegnamento efficace in Università Nel presente contributo si avvia una riflessione iniziale sulla complessità delle funzioni attribuite oggi ai docenti universitari. Si focalizza quindi l'analisi sulle competenze didattiche, sottolineando la rilevanza sociale delle stesse e l'esigenza di formarle adeguatamente, specie all'avvio della carriera accademica, e di sostenerle nell'esercizio professionale. Si cerca quindi di individuare, sulla base dei risultati di ricerca internazionale, le caratteristiche che dovrebbe avere un corso per la formazione dei docenti Universitari che possa rivelarsi efficace nel promuovere competenze didattiche innovative, in vista di un incremento della qualità degli apprendimenti degli studenti. Si propone infine un modello di formazione iniziale dei docenti, sperimentato con esiti promettenti all'Università di Torino.